Potential of non-port slot booking systems for TAS - Ann-Kathrin Lange; Stephan Krüger; Anne Kathrina Schwientek; Carlos Jahn (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: Truck appointment systems (TAS) are a reliable method for seaport container terminals to reduce peaks in truck arrivals. Thereby, the operation costs for terminals and the waiting times for trucking companies are reduced. The focus of this study is to optimize TAS by analyzing and transferring the components of nonport time slot booking systems. Methodology: A comprehensive systematic literature analysis is applied to identify the potential of non-port time slot booking systems. Three industries are identified whose time slot booking systems are well transferable to TAS. The most promising industry, the health care sector, and specific approaches are selected for a benchmark. Findings: The results show that in particular the time window booking systems from the health care sector have a good transferability to TAS in ports. Of the approaches examined, the overbooking of appointments in fixed time windows was rated most positively in the benefit analysis. Originality: Past studies usually treat TAS in ports as a completely new subject area. Findings from other industries are rarely taken into account. A systemic study on the transferability of selected approaches from other sectors has not yet been carried out for TAS.
urn:nbn:de:gbv:830-882.054831; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Truck appointment system; Container terminal; Benchmark analysis; Health care